(untitled) (Al-Qamar, 2021)
The art of Divine Writing-Calligraphy has exceptional features that truly revolve around the Islamic ideology. It is represented in diverse visionary, imaginative and creative ways. In many parts of the world the importance of hand writing or calligraphy is waned due to the modern approach in the fields of technology, science as art as well. Present day, calligraphers and artists producing such art works that are the combination of traditional scribal writing and transformed it into stylized form of calligraphic art. By utilizing assorted methods and techniques they are contributing to flourish and strengthen this art form. Therefore, in Islamic culture it is regarded as the major art form and has as a central position. By the time it is not diminished but still alive, significant and vibrant as it was from the advent of Islam.